New Finds Regarding the Architecture and Sculptures of Ancient Tenea - Korka, Eleni; Lefantzis, Michalis; Corso, Antonio (Actual Problems of Theory and History of Art, 2021)
Excavations in 2019 and 2020 in ancient Tenea revealed a main part of the city’s central web with public buildings totaling approximately 1.100 square meters. In particular, part of a public bath complex of Roman times was excavated, as well as part of an area of the Archaic times of religious significance. Several fragmentary statues have been found in the excavation of ancient Tenea and illustrate the visual culture of this centre from the severe style period to the late Hellenistic times. Moreover a relief of Dionysus held by a Satyr is walled in the main Church of Chiliomodi and should be dated in the Antonine times. During the recent period of the Tenea excavation, some important architectural blocks have been found, including Ionic and Doric capitals and column drums from different buildings. Among these limestone blocks there were fragments of triglyphs, a part of a Doric epistyle and part of a Doric column capital derived probably from the same building. Measuring the glyphs of the triglyph fragments in which a part of the metopes is saved, incorporated to the blocks, in relation with the taenia and the guttae of the epistyle, we found out that they belong to the same entablature of a middle scale Doric façade. To this façade probably belongs also the fragment of a Doric capital, without column’s rings. The beginning of the flutes is elaborated with a tooth chisel and only a part of the echinus and the hypotrachelion is saved. The width of the triglyphs is measured to 56–57 cm, identical dimension to the hypotrachelion of the capital at the level of the apophyge. Also at these blocks some lifting grooves have been found (named “lykos” in Greek), dated from the late archaic period until the middle of classic. During the research for comparanda to these blocks we initially thought that they could belong to a Doric propylon. After a preliminary analysis we can say that they look similar to those at the prostylon of the Thesaurus of Megara, at Delphi. The blocks of Tenea have the same dimensions and they form a similar building to this Thesaurus. Based on the exact type of this monument, following the same dimensions and geometry for the formation of the front view we tried to create an hypothetical representation of the blocks as part of the proposed entablature and finally, present as an hypothesis the entire front view of the monument, which was probably an archaic naiskos, situated very near to the present excavation site.
Keywords: Tenea; Baths; temple of Apollo; Artemis; Aphrodite; Dionysus; Satyr